Developing Continued Professional Development (CPD) Program For English Language Teachers: A Model For Future Action Research - Karolina, Venny; Alif, Muaffi; Sudharni; Queiroz, Carla (International Journal of Educational Research & Social Sciences, 2021)
A Continued Professional Development (CPD) in the educational context is a continual program aimed to develop teachers' quality, including English language teachers, in their teaching practices to improve students' academic achievement. A traditional or teacher-centred CPD is criticized for its failure to provide teachers' active participation. Although this program may allow teachers to learn from outside experts, it still fails to meet teachers' and classrooms' needs. The program may not be in line with the challenges and experiences teachers face in their classroom's real teaching practices. Past researchers started to identify effective professional development which invites teachers' active participation. CPD through action research offers English teachers to get involved actively from planning to the program's evaluation so that they can improve their knowledge, English language proficiency and teaching skills that fit the condition and teachers' context. This paper offers a design to develop an action research model of CPD.